Implementasi Model Blended Learning: Upaya Meningkatkan Hasil Belajar PAI Siswa SMP Negeri 2 Aceh Jaya - Firza Rahmi; Tengku Hafinda (Seutia Hukamaa Cendekia, 2023)
The research aims to examine the implementation of the model blended Learning in PAI learning at SMP Negeri 2 Aceh Jaya as an effort to improve learning outcomes. The type of research used is classroom action research with a quantitative design. The research results show that implementing the blended learning model improves student learning outcomes in the first cycle meeting offline. Teacher activity obtained an average number of 3.53 in the high category (88.3%), student activity got an average number of 1.84 in the low category (46.21), and at meeting online, teacher activity obtained an average number of 3.66 in the high category (91.66%), student activity obtained an average number of 1.57 in the low category (39.44%). In Cycle II meeting online, the average teacher activity was 3.88 in the high category (97.2%), the average student activity was 2.74 in the medium category (46.21%), and at the meeting offline, teacher activity was on average 3.68 in the high category (92.08%) and student activity on average 3.19 in the high category (80.93%). The pretest was 20% complete in the first cycle and 45% post-test. Cycle II, pretest completeness value of 45% and 90% post-test. Overall, student learning outcomes improved by 70%.